2014
DOI: 10.5194/acp-14-5433-2014
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of pollen to atmospheric ice nuclei concentrations

Abstract: Abstract. Recent studies have suggested that the icenucleating ability of some types of pollen is derived from non-proteinaceous macromolecules. These macromolecules may become dispersed by the rupturing of the pollen grain during wetting and drying cycles in the atmosphere. If true, this mechanism might prove to be a significant source of ice nuclei (IN) concentrations when pollen is present. Here we test this hypothesis by measuring ambient IN concentrations from the beginning to the end of the 2013 pollen s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
126
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 94 publications
(136 citation statements)
references
References 59 publications
(64 reference statements)
7
126
0
Order By: Relevance
“…It is a mixture of minerals with a considerable share of microcline, a K feldspar with a high ice nucleation ability as demonstrated in laboratory experiments (Atkinson et al, 2013;Zolles et al, 2015;Harrison et al, 2016). Pollen is among the primary biological aerosol particles that nucleate ice (Hader et al, 2014). Its importance for precipitation on the regional scale has been suggested in a number of studies (Pöschl et al, 2010;Prenni et al, 2013;Huffman et al, 2013;Hader et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is a mixture of minerals with a considerable share of microcline, a K feldspar with a high ice nucleation ability as demonstrated in laboratory experiments (Atkinson et al, 2013;Zolles et al, 2015;Harrison et al, 2016). Pollen is among the primary biological aerosol particles that nucleate ice (Hader et al, 2014). Its importance for precipitation on the regional scale has been suggested in a number of studies (Pöschl et al, 2010;Prenni et al, 2013;Huffman et al, 2013;Hader et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Pollen is among the primary biological aerosol particles that nucleate ice (Hader et al, 2014). Its importance for precipitation on the regional scale has been suggested in a number of studies (Pöschl et al, 2010;Prenni et al, 2013;Huffman et al, 2013;Hader et al, 2014). Birch pollen is one of the most efficient pollen species at nucleating ice as high as 264 K (Diehl et al, 2001(Diehl et al, , 2002von Blohn et al, 2005;Pummer et al, 2012Augustin et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the influence of the random placement of particles in the drop and agglomeration on the n s estimation for suspension measurements seems small. To support this, and Hader et al (2014) simulated the role of a statistical distribution in drops. The authors demonstrated that the random component due to drop placement seemed to be small relative to the statistical variation due to nucleation probability.…”
Section: Potential Effect Of Agglomeratesmentioning
confidence: 99%
“…Extensive experimental conditions were realized by NC State-CS Hader et al, 2014). Unique aspects of this instrument are the sampling of drops within a squalene oil matrix that allows for experiments using cooling rates as slow as 0.01 K min −1 and an automated freeze detection algorithm that allows for the rapid processing of more than 1000 possible drops per experiment to improve sample statistics.…”
Section: Nc State-csmentioning
confidence: 99%